Kilka uwag o „wypadku mniejszej wagi” - Brzezińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The aim of this article is to describe aspecific variant of an offence treated less severely than a corresponding standard offence, which is referred to as the “act of lesser gravity.” The author indicates structural elements of the said category of crime and also points out doubts connected with determining the level of culpability which justifies the occurrence of an “act of lesser gravity.” Moreover, the author takes into account the analysis of several concepts concerning the catalogue of circumstances justifying the qualification of an offence as an “act of lesser gravity” and, at the same time, functioning in the criminal law doctrine at the times of particular legally binding penal codes among others, acomprehensive concept, an objective concept as well as an objective-subjective concept, which is referred to as an extensive one.
Keywords: akt mniejszej wagi; przestępstwo traktowane mniej surowo; stopień winy